Targeting formyl peptide receptor 2 reduces leukocyte‐endothelial interactions in a murine model of stroke. Issue 5 (17th February 2015) - Smith, Helen K.; Gil, Cristiane Damas; Oliani, Sonia M.; Gavins, Felicity N. E.
ABSTRACT: Ischemia/reperfusion (I/R) injury following stroke can worsen patient outcome through excess inflammation. This study investigated the pharmacologic potential of targeting an endogenous anti‐inflammatory circuit via formyl peptide receptor (FPR) 2/lipoxin receptor (ALX) (Fpr2/3 in mouse) in global cerebral I/R. Mice (C57BL/6 and Fpr2/3 ‐/‐ ) were subjected to bilateral common carotid artery occlusion, followed by reperfusion and treatment with FPR agonists: AnxA1Ac2‐26 [Annexin A1 mimetic peptide (Ac‐AMVSEFLKQAWFIENEEQEYVQTVK), 2.5 μg/kg] and 15‐epimer‐lipoxin A4 (15‐epi‐LXA4 ;FPR2/ALX specific, 12.5 and 100 ng/kg). Leukocyte‐endothelial (L‐E) interactions in the cerebral microvasculature were then quantified in vivo using intravital fluorescence microscopy. 15‐epi‐LXA4 administration at the start of reperfusion reduced L‐E interactions after 40 min (which was sustained at 2 h with high‐dose 15‐epi‐LXA4 ) to levels seen in sham‐operated animals. Anx‐A1Ac2‐26 treatment decreased leukocyte adhesion at 40 min and all L‐E interactions at 2 h (up to 95%). Combined treatment with AnxA1Ac2‐26 plus FPR antagonists t ‐Boc‐FLFLF (250 ng/kg) or WRW4 (FPR2/ALX selective, 1.4 μg/kg) abrogated the effects of AnxA1Ac2‐26 fully at 40 min. Antagonists were less effective at 2 h, which we demonstrate is likely because of their impact on early L‐E interactions. Our findings indicate that FPR2/ALX activity elicits considerable control over vascular inflammatory responses during cerebral I/R and, therefore, provide evidence that targeting FPR2/ALX may be beneficial for patients who suffered from stroke.—Smith, H. K., Gil, C. D., Oliani, S. M., Gavins, F. N. E. Targeting formyl peptide receptor 2 reduces leukocyte‐endothelial interactions in a murine model of stroke. FASEB J. 29, 2161‐2171 (2015). www.fasebj.org